Fostering Leadership in Psychiatry: Outcomes of the West Midlands Leadership Programme for Higher Trainees - Feroz Nainar; Rosie England; Kieran Groom; Lorna Almond (BJPsych Open)
Aims: To outline the development and implementation of the West Midlands Psychiatry Leadership Programme, a pioneering initiative believed to be unique within UK psychiatry training, and to evaluate participant feedback on its impact and benefits.